2021
DOI: 10.1021/acsmaterialslett.1c00332
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Enhancement through Confined Oligomerization in Nanochannels: An Anthryl Oligomer in a Metal-Organic Framework

Abstract: Nanoconfinement offers opportunities to tune physical properties of molecular entities by altering their assembled structures. This also applies to acene-based molecules with potentially rich π–π interactions. Unlike most of the previous cases with acene-based guests directly incorporated into hosts, we take a further step by oligomerizing a fluorescent anthryl monomer, 9-vinylanthracene, inside nanochannels of a metal–organic framework, which is a pillared three-dimensional kagome net of [Zn2(bdc)2(dabco)] (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…46 Wang used the 9-vinylanthracene as a monomer and polymerized it in a nanopore channel in an MOF adsorbent. 47 A new, smaller micropore of 0.8 nm was generated in the original 1.2 nm micropore. Similarly, Nipuni successfully loaded the polystrene into the micropore of the MOF-5 and finally increased the micropore volume at 1 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Wang used the 9-vinylanthracene as a monomer and polymerized it in a nanopore channel in an MOF adsorbent. 47 A new, smaller micropore of 0.8 nm was generated in the original 1.2 nm micropore. Similarly, Nipuni successfully loaded the polystrene into the micropore of the MOF-5 and finally increased the micropore volume at 1 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, confined polymerization has been found to be a novel technique for changing the pore diameter and chemical property by a postmodification method. Zhang has made macroporous silica a carrier while acrylic acid and allyl acetoacetate were used as monomers to prepare an ion-exchange resin (SiAcyl) which has a great palladium adsorption effect from electroplating wastewater . Wang used the 9-vinylanthracene as a monomer and polymerized it in a nanopore channel in an MOF adsorbent . A new, smaller micropore of 0.8 nm was generated in the original 1.2 nm micropore.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, a small change in the polarity and shape of MOF nanochannels can result in a large shift in emission despite similar pore sizes. From a survey of the field, it is observed that excimers formation of various dyes, such as naphthalene, , anthracene (Ant), pyrene, , and linkers, , within MOFs leads to progression in a number of fields, including modulation of emitting color and thermosensitive luminescence. Based on these findings, MOFs-confined dyes should be a good platform to explore the relationship between components and properties.…”
Section: Introductionmentioning
confidence: 99%